Simultaneous saccharification and fermentation of cassava stems (2013)
ABSTRACT: This research evaluates the effects of the inoculum size and enzymatic activity on the concentration of ethanol obtained through the simultaneous saccharifi cation and fermentation of alkali-pretreated cassava stems. Other goals for this study include the determination and validation of the optimal conditions for and the evaluation of the process of ethanol production in a bioreactor. Alkaline-pretreated cassava stems were used as the substrate in a solid to liquid ratio of 1:10; the enzymatic complex Accellerase 1500 and the yeast Ethanol Red were evaluated at two levels at a temperature of 38° C and a pH of 4.0 in an Erlenmeyer fl ask. The following were evaluated as process controls: simultaneous saccharifi cation and fermentation of non-pretreated stems and separate saccharifi cation and fermentation of pretreated stems. A regression analysis was conducted, and the resulting model was maximized using genetic algorithms. At the optimal conditions identifi ed in an Erlenmeyer fl ask, the production of ethanol in a 5-liter bioreactor was subsequently evaluated. An experimental concentration of ethanol of 1.88±0.04% v/v (1.99% v/v simulated optimum) was obtained using an inoculum concentration of 1.59 g/L and an enzyme concentration of 13.3 FPU/g. This value was approximately four times the quantity of ethanol produced without pretreatment or by the separate saccharifi cation and fermentation of pretreated cassava stems. The evaluation of the process in the bioreactor yielded an ethanol concentration 20% less than that reached in the Erlenmeyer flask.